The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31186/agrisep.20.01.25-40
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Telepon Seluler Untuk Pemasaran Serta Dampaknya Terhadap Kesejahteraan Petani

Abstract: The development of information technology has encouraged farmers to be able to use cellular phones to support agricultural activities. However, only a few farmers use their cellphones for marketing activities. This study aims to analysis factors influence farmers to use cell phones in marketing activities, and whether cell phone use has an impact on farmers' welfare. The analytical method used is the logit regression model and Propensity Score Matching (PSM). The results showed that what influenced farmers' de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
2
6
1
Order By: Relevance
“…The fundamental problem that is often encountered when using the PSM method is not being able to measure the potential outcomes of households using mobile phones (Y 1i ) and the control group (Y 0i ) at the same time (Feryanto & Rosiana, 2021). In this regard, only one can be observed, using an estimation model that allows seeing the average value of the impact of cell phone usage.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fundamental problem that is often encountered when using the PSM method is not being able to measure the potential outcomes of households using mobile phones (Y 1i ) and the control group (Y 0i ) at the same time (Feryanto & Rosiana, 2021). In this regard, only one can be observed, using an estimation model that allows seeing the average value of the impact of cell phone usage.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Several previous studies have identified the determinants of using information and communication technology in the form of mobile phones by farmers. Several factors, including age, influence farmers' decisions to use mobile phones, length of education, income, marital status, home ownership status, and land area (Aminou et al, 2018;Folitse et al, 2019;Umaroh & Afifah, 2020;Feryanto & Rosiana, 2021;William et al, 2021). Folitse et al (2019), in their study using logistic regression analysis it was found that the coefficient of the age variable had a negative and significant relationship with the use of mobile phones as a communication tool for agricultural information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations